Mangrove management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Mangrove forest management guidelines FAO Forestry Paper 117 1994 319pp ISBN 92 5 103445 1 FAO Publications, FAO, Via delle Terme di Caracalla, 00100 Rome, ITALY